The construction of pyramid structure of micro aluminum oxide. Issue 6 (15th March 2022) - Zhou, Xing; Li, Mengyao; Wang, Dong; Pu, Mengyuan; Fang, Changqing; Yu, Ruien; Xie, Li; Ru, Yan
Abstract: The assembly of colloidal particles to crystal structure on micrometer scale is attractive due to the unique and complex structure with stable physical and chemical properties, and even good anti-reflectivity. In this work, the pyramidal Al2 O3 film was prepared via the designed process combining the sol-gel method and hydrothermal reaction. We employed Al(NO3 )3 and H2 NCONH2 as precursors and precipitant respectively on monocrystalline silicon wafer without etching. The bulk structure and components of the pyramidal Al2 O3 film were investigated and analyzed by scanning electron microscope, energy dispersive X-ray spectrometers, X-ray diffraction, transmission electron microscope and X-ray photoelectron spectroscopy, etc. The fabricated Al2 O3 films were composed of pyramidal structures, which mainly consisted of nanorods and nanospheres with both side length and thickness in micro scales. The surface reflectance and water contact angle results suggested that the surface of the film was hydrophilic and the average surface reflectance was 17.9%.